Sustained censorship in RU (2022-02) (Russia) - Voidly (2022)
CRITICAL severity censorship detected in Russia. Confidence: 75%. Data sourced from OONI.
Censorship Incident ID: RU-2022-0002
Keywords: censorship; RU; censorship; critical